2012
DOI: 10.1155/2012/460919
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Silicon Single-Junction Thin-Film Solar Cell Exceeding 10%Efficiency by Design Optimization

Abstract: The conversion efficiency of a solar cell can substantially be increased by improved material properties and associated designs. At first, this study has adopted AMPS-1D (analysis of microelectronic and photonic structures) simulation technique to design and optimize the cell parameters prior to fabrication, where the optimum design parameters can be validated. Solar cells of single junction based on hydrogenated amorphous silicon (a-Si:H) have been analyzed by using AMPS-1D simulator. The investigation has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…It has been reported that increasing the absorber thickness in a BaSi 2 /CdS/fluorine‐doped tin oxide solar cell causes V OC to decrease gradually . A very similar decreasing fashion is also observed for a‐Si:H solar cells . However, the experimentally fabricated FeSi 2 solar cells gave V OC in the range 176–450 mV, whereas it was 391–900 mV for the theoretical works.…”
Section: Resultssupporting
confidence: 75%
“…It has been reported that increasing the absorber thickness in a BaSi 2 /CdS/fluorine‐doped tin oxide solar cell causes V OC to decrease gradually . A very similar decreasing fashion is also observed for a‐Si:H solar cells . However, the experimentally fabricated FeSi 2 solar cells gave V OC in the range 176–450 mV, whereas it was 391–900 mV for the theoretical works.…”
Section: Resultssupporting
confidence: 75%
“…the accompanying spatial gradient in the bandgap that may also aid charge separation and reduce the EHP recombination rate. 23,24 The study described herein concerns an especially simple type of solar cell that has received scant attention from researchers to date: a Schottky-barrier solar cell. 25 The Schottky barrier is provided by a metal-semiconductor junction.…”
Section: Introductionmentioning
confidence: 99%
“…One such phenomenon, which remains a persistent issue during the manufacture of amorphous silicon thin films, is non-uniformities which develop in the thickness and morphology of deposited layers across the radius of the wafer. Spatially non-uniform deposition has been well characterized [14][15][16] and shown to affect the efficiency of solar cell products [17], resulting in poor device quality and increased costs [18]. As such, there exists a need for accurate PECVD reactor models which are capable of predicting the codependent behavior of the macroscopic gas phase and microscopic thin film growth.…”
Section: Introductionmentioning
confidence: 99%